A phase II multicenter randomized study to evaluate the safety and efficacy of combining thermotherapy and a short course of miltefosine for the treatment of uncomplicated cutaneous leishmaniasis in the New World. - Liliana López; Braulio Valencia; Fiorela Alvarez; Ana Pilar Ramos; Alejandro Llanos-Cuentas; Juan Echevarria; Iván Vélez; Marina Boni; Joelle Rode; Juliana Quintero; Alejandra Jiménez; Yulied Tabares; et al. (Public Library of Science (PLoS), 2022)
Background Systemic pentavalent antimonials, mainly meglumine antimoniate, continue to be the first-choice drugs for treatment of cutaneous leishmaniasis (CL) despite their toxicity, difficulty of administration and high cost. In the search for therapeutic alternatives, combining two treatment interventions has emerged as a potential alternative to either reduce the use of antimonials with the associated toxicities, or to increase efficacy. Here, we report the results of a recently completed trial assessing the efficacy and safety of a combination of thermotherapy (TT) plus a short course of miltefosine (MLT) for the treatment of uncomplicated CL in Colombia and Peru. Methods A multicenter, randomized, evaluator-blinded, phase II, controled clinical trial was conducted. Adult volunteers with a parasitologically confirmed diagnosis of uncomplicated CL were randomly allocated to receive either a single session of TT or a combination of TT plus a short course of MLT (3 weeks). Therapeutic response outcomes and safety were assessed. Results 130 subjects were included in the study, of whom 64 were randomly assigned to the TT arm and 66 to the TT + MLT arm. Cure at 3 months' follow-up was achieved in 57.8% (n = 37) and 80.3% (n = 53) in the TT and TT + MLT groups, respectively, in the intention to treat analysis. The TT + MLT regimen was better that TT alone (p = 0.0055). The presence of vesicles at the site of heat application was the most common adverse event reported associated with the use of TT; while vomiting (31.8%) and elevation of liver enzymes (28.8%) were the most frequent adverse events reported associated with the use of MLT. Conclusion The combination of TT plus a short course of MLT was shown to be significantly better than TT alone for the treatment of uncomplicated CL in the New World. Trial registration Registered in clinicaltrials.gov NCT02687971.